Hubungan Usia, Paritas, dan Obesitas dengan Kejadian Preeklamsia di RSUD Kayuagung Tahun 2021 - Cynthia Uning Dasarie; Siti Aisyah Hamid; Erma Puspita Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
According to the World Health Organization (WHO) in 2017 around 810 women died and at the end of the year reached 295,000 people, of which 94% occurred in developing countries. The high maternal mortality rate (MMR) and infant mortality rate (IMR) are caused by complications in pregnancy and childbirth. Preeclampsia is one of the main causes of death in mothers besides bleeding and infection. Preeclampsia is hypertension that occurs after 20 weeks of gestation accompanied by proteinuria. This study aims to find out the relationship between age, parity, and obesity with the incidence of preeclampsia at the Kayuagung Regional General Hospital in 2021. The method in this study used an analytical survey using a cross-sectional approach with a population of 1624 pregnant women and a sample of 94 pregnant women using the total technique. sampling. Data analysis used the chi square statistical test with p value â‰¤ Î± value (0.05). The results of this study were of 59 respondents who were at high risk, 31(52.5%) of respondents had preeclampsia p value = 0.031, of 56 respondents with high risk parity 40 (71.4%) of respondents had preeclampsia p value = 0.032, meanwhile, from 60 respondents with obesity 24 (40%) respondents had preeclampsia p value = 0.000. It is hoped that midwives can increase the provision of education to pregnant women regarding danger signs in pregnancy and healthy lifestyles during pregnancy so that the incidence of preeclampsia can be reduced and maternal mortality rates can be reduced.